Critical Discourse Analysis of Tjitjik Sri Tjahjandari’s Statement: “Pendidikan Tinggi Adalah Tertiary Education” - Diyah Herawati; Roswita Lumban Tobing; Yeni Artanti (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
In May 2024, significant tuition fee hikes at Indonesian state universities led to widespread protests and public outcry. Prof. Tjitjik Srie Tjahjandari's response, emphasizing that higher education is a choice rather than a necessity, drew significant attention and criticism.The research aims to critically analyze the ideological meanings in Tjahjandari's statement and explore its impact on public perception and educational policy in Indonesia. The study uses Fairclough's CDA framework to analyze the linguistic features in textual analysis level, production and distribution processes in discursive strategy, and broader social contexts of the statement. Data collection includes the statement's transcript, media reports, and public responses. Textual analysis reveals the use of technical and institutional language that aligns with neoliberal ideologies, lead to describe higher education as an optional, market-driven pursuit. Discursive practice analysis shows the statement's wide media dissemination and critical public interpretation that suggest a perceived shift away from viewing higher education as a public good. Social practice analysis indicates that the statement supports hegemonic processes that commodify education and reduce the state's role in ensuring access. The study concludes that Tjahjandari's statement reflects and constructs ideological meanings that devalue higher education's societal importance and impact its accessibility. Public reactions highlight a demand for more equitable and inclusive educational policies. This research contributes to understanding the role of governmental discourse in shaping educational policy and societal attitudes, advocating for policies that support broader access to higher education.